Os estudos sobre neoliberalismo e educação escolar em sete periódicos educacionais entre 2016 e 2023 - Pedrosa, Izadora Sarmento Loureiro (2025)
This research falls within the field of State, Policies, and History of Education, and seeks to investigate the relationship between neoliberalism and school education. It is a bibliographic review that analyzes articles published in scientific journals between the years 2016 and 2023. The chosen time frame was established based on the understanding that this period marks the advancement of (neo)conservative policies in Brazil. A key challenge of this study is to address the following proposition: considering the academic-scientific literature that explores the relationship between neoliberalism and school education, this research focuses on analyzing the content of these studies—particularly the research questions and problems posed—in order to subject scientific thought itself to rational reflection. It asks: how is the Brazilian scientific production about school education on the (s) relationship(s) between education and neoliberalism? Thus, the research began with a theoretical-conceptual analysis of the foundations of neoliberalism and school education, examining their historical contexts and possible consequences for the school environment, as schools have increasingly been shaped into models that reproduce neoliberal policies and are used as instruments for market expansion. The study analyzes 41 full articles published in well-regarded academic journals in the field, using the bibliographic research methodology (Lima and Mioto, 2007) and based on the content analysis method (Bardin, 1989). The selected journals include: Revista Brasileira de Educação (ANPEd); Revista Educação e Pesquisa (USP), from the Southeast region; Revista Inter-Ação (UFG), from the Center-West region; Revista Práxis Educativa (UEPG), from the South; Revista Cocar (UEPA), from the North; Revista Germinal (UFBA), from the Northeast; and Revista Retratos da Escola, published by the National Confederation of Education Workers (CNTE). The main theoretical references that supported the analysis of the subject include works by Antunes (1999; 2022), Apple (2003), Cury (2008), Dardot and Laval (2006), Freitas (2018), Harvey (1992; 2014), Ianni (2004), Laval (2019), Lima (2012), Lima and Mioto (2007), Marx (2010), Miranda (2020), Saad Filho and Morais (2018), Sampaio et al. (2002), among others. It is understood that neoliberalism represents the most authoritarian phase of capitalist development to date, as it seeks to convert and reduce education—a fundamental element in shaping society—into a mere service. The main contributions of this research lie in highlighting how recent academic production has addressed and problematized the relationship between neoliberalism and Brazilian school education, synthesizing and emphasizing the predominant themes found in these studies: Curriculum Policies, Training by the School, Reform Teacher Education, Precarization/Privatization of Education, Social Exclusion/Inequality, and Conservatism/Neoconservatism.